QUANTITATIVE ANALYSIS OF THE STRENGTH GENERATING C-S-H-PHASE IN CONCRETE BY IR-SPECTROSCOPY - Schmidt-Döhl, Frank Michael; Schulenberg, David; Tralow, Franziska; Neubauer, Jürgen; Wolf, Julian; Ectors, Dominique (Acta Polytechnica CTU Proceedings, 2022)
The C-S-H-phase is the most important strength generating phase in concrete and other cementitious materials. The analysis of C-S-H is therefore an important instrument of innovations in the field of concrete and its durability and sustainability. The quantification and insights in C-S-H are hindered by the predominantly amorphous structure of C-S-H. Only the time consuming and expensive solid state nuclear magnetic resonance spectroscopy (NMR) gives a chance to get results, but is restricted to model substances. A new technique, based on the cheap and widespread infrared-spectroscopy (IR) was developed. The quantitative analysis is based on the silicon content in the different structural units of C-S-H and a calibration with natural and synthetic materials with known silicon content in these units. The technique allows to investigate specimens from real structures. Specimens with quartz or limestone aggregate can be analyzed directly. In other cases the aggregates must be separated, for example with heavy liquid separation. Tests with different mortars showed a good correspondence of measured and expected values of C-S-H concentration.
CRIS-Team Scopus Importer:2022-09-02
Keywords: Calcium-Silicate-Hydrate (C-S-H); quantitative analysis; spectroscopy